WEAVE: the next generation wide-field spectroscopy facility for the William Herschel Telescope - Dalton, G; Trager, S; Abrams, D; Carter, D; Bonifacio, P; Aguerri, J; MacIntosh, M; Evans, C; Lewis, I; Navarro, R; Agocs, T; Dee, K; et al. (2012)
We present the preliminary design of the WEAVE next generation spectroscopy facility for the William Herschel Telescope (WHT), principally targeting optical ground-based follow up of upcoming ground-based (LOFAR) and space-based (Gaia) surveys. WEAVE is a multi-object and multi-IFU facility utilizing a new 2 degree prime focus field of view at the WHT, with a buffered pick and place positioner system hosting 1000 multi-object (MOS) fibres or up to 30 integral field units for each observation. The fibres are fed to a single spectrograph, with a pair of 8k(spectral) x 6k (spatial) pixel cameras, located within the WHT GHRIL enclosure on the telescope Nasmyth platform, supporting observations at R-5000 over the full 370-1000nm wavelength range in a single exposure, or a high resolution mode with limited coverage in each arm at R-20000. © 2012 SPIE.